Establish a partnership to achieve the SDGs, through the implementation of a teaching strategy mediated by a didactic sequence - Páez, Daniel Alejandro Sánchez; Ruiz, Marisela Restrepo; Bula, Ligia Rosa Martinez; Yanez, Fabian Hincapie (Edelweiss Applied Science and Technology, 2026)
This project aims to characterize the school community problems and raise awareness about the importance of implementing SDGs. Thereby, the research arose from the need to raise awareness between the private, and public sectors might help in some way to respond to this issue. A teaching strategy was proposed and designed to respond assertively to students' urgency in recognizing the value of making agreements to achieve the well-being of society. In the methodology section, the paradigm was qualitative, following the participatory action research approach. Regarding the data collection section, the techniques and instruments used were: the direct-observation, a questionnaire as pre and post-test. In addition to the didactic sessions designed and implemented intended to fulfill the pre-established lesson objectives. Concerning the outstanding results, the diagnosis was conducted based on the identification of the public versus private entities that developed projects related to the SDGs development, with which effective alliances were established. It also favored the awareness and appropriation of students in terms of increasing local, national, and international connections. In sum, establishing partnership for alliances is crucial not only for accomplishing them, but for the process traceability in terms of human resource efficiency in actions where institutions converge.